Meteorological Patterns Associated with Intense Saharan Dust Outbreaks over Greece in Winter - P. T. Nastos (Advances in Meteorology)
The Mediterranean Basin and southern Europe are often affected by Saharan dust outbreaks, which influence the aerosol load and properties, air quality standards, visibility and human health. The present work examines, mainly of the meteorological point of view, three intense dust outbreaks occurred over Greece with duration of one or two days, on 4 and 6 February and 5-6 March 2009. The synoptic analysis on the dusty days showed the presence of low-pressure systems in the west coasts of Europe and the north Tyrrhenian Sea, respectively, associated with a trough reaching the north African coast. The result of these conditions was the strong surface and mid troposphere winds that carried significant amounts of dust over Greece. During the dusty days extensive cloud cover associated with the dust plume occurred over Greece. The air-mass trajectories showed a clear Saharan origin in all atmospheric levels, while the satellite (MODIS Terra/Aqua) observations as well as the model (DREAM) predictions verified the intense dust outbreaks over eastern Mediterranean and Greece. The ground based particulate matter concentrations in Athens were excessively increased on the dusty days (PM10: 150–560 μg/m3), while significant dry and wet deposition occurred as forecasted by DREAM model.